Pengukuran Kualitas E-Commerce Shopee Terhadap Kepuasan Pengguna Menggunakan Metode Webqual 4.0 - Ar Rachman Abdu’a; Sri Wasiyanti (Paradigma, 2019)
- Shopee is one of The e-commerce in Indonesia That has a big role in The Business of online buys and sells.  The rise of e-commerce, The rapid Development of Technology, less adaptive in The implementation of Technology website Services, makes Shopee ranked has decrease. The increasement of The Service is expected to rise The rank and satisfaction of Shopee users. This Research Measures Shopee website quality through webqual 4.0 (usability, information quality, interaction quality) and user satisfaction variables. Data collection method using primary data in The form of questionnaires distributed to respondents who amounted to 113 through Social media or media chat and secondary data taken from books and reference journals related to Research problem. The Resault of this Research is, from 3 dimension of webqual 4.0 only Information Quality dimension assessed have an effect on to user satisfaction of Shopee e-commerce website, whereas Usability and Interaction Quality dimension is not influence to user satisfaction of Shopee e-commerce website. this could be due to some respondents considered Shopee e-commerce website difficult to use in interacting with users and still difficult to run menus available on Shopee e-commerce website and also in The respondents There are 50 mens where they are people who are not used Shop online that seldom or never use The Shopee e-commerce website. Resault of test f and significant level is obtained, there is positive influence to user satisfaction of Shopee e-commerce website simultaneously.